THE TRANSFORMATIVE POWER OF ARTIFICIAL INTELLIGENCE (AI) TO ELEVATE ENGLISH LANGUAGE LEARNING - Ulfa, Kurnia (Majalah Ilmiah METHODA, 2023)
The article delves into the transformation impact of Artificial Intelligence (AI) on enhancing students’ proficiency in learning English language. Recognizing the global importance of English proficiency, educators are increasingly turning to AI as a powerful tool to revolutionize language education. The integration of AI brings forth personalized learning paths, intelligent tutoring systems, gamification strategies, language learning apps, and automated assessments. These advancements cater to individual learning needs, provide real time feedback, foster engagement through gamified experiences, and offer accurate assessments of language skills. The synergistic relationship between AI and language education represents a paradigm shift in the ways students acquire and master the English language, positioning them for success in an increasingly interconnected world.